Investigating ion channel conformational changes using voltage clamp fluorometry. (November 2015) - Talwar, Sahil; Lynch, Joseph W.
Abstract: Ion channels are membrane proteins whose functions are governed by conformational changes. The widespread distribution of ion channels, coupled with their involvement in most physiological and pathological processes and their importance as therapeutic targets, renders the elucidation of these conformational mechanisms highly compelling from a drug discovery perspective. Thanks to recent advances in structural biology techniques, we now have high-resolution static molecular structures for members of the major ion channel families. However, major questions remain to be resolved about the conformational states that ion channels adopt during activation, drug modulation and desensitization. Patch-clamp electrophysiology has long been used to define ion channel conformational states based on functional criteria. It achieves this by monitoring conformational changes at the channel gate and cannot detect conformational changes occurring in regions distant from the gate. Voltage clamp fluorometry involves labelling cysteines introduced into domains of interest with environmentally sensitive fluorophores and inferring structural rearrangements from voltage or ligand-induced fluorescence changes. Ion channel currents are monitored simultaneously to verify the conformational status. By defining real time conformational changes in domains distant from the gate, this technique provides unexpected new insights into ion channel structure and function. This review aims to summarise the methodology and highlight recent innovative applications of this powerful technique. This article is part of the Special Issue entitled 'Fluorescent Tools in Neuropharmacology'. Highlights: Voltage clamp fluorometry reports ion channel conformational changes in real time. It thus defines domains involved in activation, modulation and desensitization. It is particularly important for resolving drug modulatory mechanisms. The incorporation of fluorescent unnatural amino acids will enhance its utility.